Evaluation of the application of Phase Change Materials (PCM) on the envelope of a typical dwelling in the Mediterranean region. (November 2016) - Panayiotou, G.P.; Kalogirou, S.A.; Tassou, S.A.
Abstract: In this work the application of macroencapsulated Phase Change Materials (PCM) on the envelope of a typical dwelling in the Mediterranean region is evaluated. This is the first time PCMs are evaluated for application under the specific climatic conditions of Cyprus. The simulation process is carried out using Transient Systems Simulation software (TRNSYS). Two types of simulations have been carried out: the energy rate control test and the temperature level control test. The energy savings achieved by the addition of the PCM layer on the envelope of the test cubicle compared to the base case (no insulation) ranged between 21.7 and 28.6%. The optimum PCM case was also combined with a common thermal insulation topology in Cyprus. The results showed that the maximum energy savings per year was achieved by the combined case (66.2%). In the temperature level control test the constructions containing PCM performed better during summer. The results of the optimum PCM case and the combined case were economically evaluated using Life Cycle Cost (LCC). The results of this analysis showed that the PCM case has a very long payback period (14 ½ years) while this is changing when it is combined with insulation where the payback period is reduced to 7 ½ years. Highlights: Application of PCM on the envelope of a typical dwelling in a hot environment. This is the first time PCM are evaluated for application for the climate of Cyprus. The energy savings achieved by applying PCM ranged between 21.7 and 28.6% while the payback period was 14 ½ years.. PCM were combined with thermal insulation and an energy savings of 66.2% was achieved and the payback period was 7 ½ years.